The mathematical modeling of the loading process of grain to the silos - Арендаренко, В. М.; Самойленко, Т. В. (Scientific Progress & Innovations, 2018)
The technological loading process of grain to the silos is based on the lift of grain at a certain height and transportation of grain to the container’s load hole. The centrifugal bucket elevators, the drag and self-flowing conveyors, the special loading devices of silos are used in this process. During all stages of this grain mass’ transportation the corn seeds are traumatized. It has negative effect on the process of grain storage. The damage of corn seeds have been influenced by the outside and inside factors connected with the certain transport machines. The physical-mechanical and biological properties of grain are inside factors. The constructional and engineering data of machines, which we use for the loading process of grain to the silos, are outside factors. The mathematical modeling of all engineering loading process of grain material to the silos has been suggested in this article. The most successful methods of study of this model are the methods of simulation modeling. The parametric model, created on the basis of simulation, takes account of the certain set members, which conform to the centrifugal bucket elevators, the drag conveyors and the loading devices of silos. It follows from this engineered model that the main problem is a correct selection of the parameters influencing on the loading process of grain to the silos. It will lead to decrease the partial and complete destruction of the corn seeds.